2014
DOI: 10.14710/ijred.3.3.175-183
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gasohol as Alternative Fuel for Gasoline Substitution: Characteristics and Performances

Abstract: ABSTRACT:Gasohol is a mixture of premium petrol (gasoline) with alcohol, in this case ethanol. The use of gasohol can reduce fuel consumption without having to modify the existing engine. Therefore, this research is conducted to study the characteristics and performance of gasohol in various mixing ratios, which includes analysis of physical properties and the use of gasohol in the machine. Results show that the addition of technical ethanol at 7.0169%v increases the value of gasohol vapor pressure on the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The viscosity, ASTM color, flash point and pour point of both fuels were not measurable in this study. The Reid vapor pressures (RVP) of these fuels were observed as 58.00 and 41.00 kPa; notably, it had been studied that the gasohol containing 2.50% of industrial ethanol 96% gives an RPV of 56.54 kPa [23]. The RPV standard issued by the US Environmental Protection Agency (EPA) is in the range of 54-62 kPa, which is comparable to that of the present investigation.…”
Section: The Fuel Parameterssupporting
confidence: 81%
See 1 more Smart Citation
“…The viscosity, ASTM color, flash point and pour point of both fuels were not measurable in this study. The Reid vapor pressures (RVP) of these fuels were observed as 58.00 and 41.00 kPa; notably, it had been studied that the gasohol containing 2.50% of industrial ethanol 96% gives an RPV of 56.54 kPa [23]. The RPV standard issued by the US Environmental Protection Agency (EPA) is in the range of 54-62 kPa, which is comparable to that of the present investigation.…”
Section: The Fuel Parameterssupporting
confidence: 81%
“…A study on the emulsion fuel blend of ethanol and gasoline with a RON of 88 was conducted previously [22]. Authors [23][24] reported obtaining a blended fuel (gasoline and ethanol) with a technical ethanol concentration of 96%. Increasing the amount of ethanol in fuel could increase the research octane number (RON), substance density, and kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…1-3. All the curves have a typical sigmoidal profile, characteristic for liquids with many components [19,20]. Reference points of the distillation curve are the initial boiling point (IBP), final boiling point (FBP) and intermediate points: T10, T50 and T90 (according to ASTM 4814) that represent the temperature at which 10, 50 and 90 respectively, distilled volume is recovered.…”
Section: Distillation Curvesmentioning
confidence: 99%
“…For this purpose, the effect of oxygenated fuels on exhaust emissions at the low ambient temperature startup and warm-up operation of the SI engine was investigated. It does not require any modifications to the engine when using gasoline/alcohol mixtures containing low amounts of alcohol (Murachman et al 2014), so ethanol and methanol (10% by vol.) were used as alternative fuels.…”
Section: Introductionmentioning
confidence: 99%